The - Ihnatko, Andy (Wiley, 2005)
The cat's out of the bag, and Andy Ihnatko gives you a hundred reasons to fall in love with the Tiger. Packed with sage advice -- and plenty of humor -- this beefy volume holds your hand through installing Tiger, helps you diagnose and cure common problems, introduces you to more shortcuts than you ever imagined, and provides tips on everything from using Spotlight to choosing a tattoo. It's not only the greatest Mac OS X guide ever, it's surely the most entertaining